EXPERIMENTATION OF THE KSIL MENTHOD (KONSEP, SIMULASI, IMPLEMENTASI, EVALUASI) IN TEACHING VISITING PROCEDURES TO STUDENTS - Astrid Wangsagirindra Pudjastawa (Universitas Veteran Bangun Nusantara, 2021)
This study aims to determine whether the KSIL (Concept, Simulation, Implementation, and Evaluation) method offered can provide a better insight into visiting ethics compared to groups of students who are taught using conventional learning models in Javanese, Javanese in class XII SMK Negeri 3 Malang Semester I of 2019/2020 Academic Year. This type of research is quasi-experimental research. The population in this study were all class XII students of the Computer and Network Engineering Department at SMKN 3 Malang. The research sample was 28 students of class XIIa and 27 students of class XIIb. The data obtained were analyzed using descriptive statistical analysis techniques and inferential statistics (t-test). The results of this study are: (1) Good visiting ethics insight of the experimental group students is very high with an average of 34.78, (2) Good visiting ethics insight in the control group students is high with an average of 28.93. (3) There is a significant difference in the value of good visiting ethics insight between groups of students taught using the KSIL (Concept, Simulation, Implementation, and Evaluation) method and groups of students taught using conventional learning. The Javanese learning model for class XII students of SMK Negeri 3 Malang. Semester I of the 2019/2020 Academic Year. This shows that the KSIL learning method (Concept, Simulation, Implementation, and Evaluation) has a positive effect on students' insights about good visiting ethics.